Deciphering Patterns and Drivers of Heat and Carbon Storage in the Southern Ocean. Issue 6 (21st March 2019) - Chen, Haidi; Morrison, Adele K.; Dufour, Carolina O.; Sarmiento, Jorge L.
Abstract: The storage of anomalous heat and carbon in the Southern Ocean in response to increasing greenhouse gases greatly mitigates atmospheric warming and exerts a large impact on the marine ecosystem. However, the mechanisms driving the ocean storage patterns are uncertain. Here using recent hydrographic observations, we compare for the first time the spatial patterns of heat and carbon storage, which show substantial differences in the Southern Ocean, in contrast with the conventional view of simple passive subduction into the thermocline. Using an eddy‐rich global climate model, we demonstrate that redistribution of the preindustrial temperature field is the dominant control on the heat storage pattern, whereas carbon storage largely results from passive transport of anthropogenic carbon uptake at the surface. Lastly, this study highlights the importance of realistic representation of wind and surface buoyancy flux in climate models to improve future projection of circulation change and thus heat and carbon storage. Key Points: Observed excess heat ( Q ′) and anthropogenic carbon storage in the Southern Ocean shows contrasting spatial patterns Eddy‐resolving model reveals that circulation change controls Q′ storage; carbon storage anomaly ( C′ ) behaves more like a passive tracer A responsive surface buoyancy flux results in a greater sensitivity of net circulation change in response to wind stress change